Uptake of human eosinophil peroxidase by human neutrophils. - Zabucchi, G. (1986)
A cytochemical analysis was carried out for study of the interaction between human eosinophil peroxidase (EPO) and human neutrophils. To this end, neutrophils with a genetic deficiency of myeloperoxidase (MPO) were used to avoid the otherwise inevitable interference of the high endogenous MPO activity of normal neutrophils. The data show that human neutrophils incubated with EPO (1 GU/ml) rapidly bind the enzyme all over the cell surface and internalize it in small vesicles. Part of bound EPO concentrates in a limited area on the cell surface and is then internalized by means of coarse tubular channels. Fusion of the small vesicles to each other or possibly with the tubular channels gives rise ultimately to EPO-containing multivesicular bodies, which, after 30 minutes of incubation, are the only peroxidase-positive structures in the cytoplasm. Under identical experimental conditions, no binding of human MPO to the neutrophils was detected. At concentrations 10 times as high as those used for EPO, a minority of neutrophils bound MPO, but the binding pattern remained diffuse on the plasma membrane and the internalization was negligible. It seems, therefore, that the EPO trapping system of human neutrophils exhibits specificity at least among leukocyte peroxidases. Furthermore, it operates at much lower concentrations of EPO than those reported for EPO uptake by mast cells and basophils. The uptake of EPO by neutrophils may serve to sequester a potentially toxic agent, thus limiting damage to the tissue in eosinophil-rich inflammatory lesions.